The Influence of Reading Interest and Study Habits against Mathematics Learning Outcomes - Arofah, Irvana; Ningsi, Besse Arnawisuda (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of reading interest and study habits on mathematics learning outcomes. The results showed that the variables of reading interest and study habits simultaneously (simultaneously) had an influence on mathematics learning outcomes which were expressed by the following regression equation model: Y = 49,014 + 0,479X1 – 0,212X2. From the results of the analysis, it can be concluded that the variables of reading interest and study habits together have a significant influence on mathematics learning outcomes. The two independent variables contributed to the learning outcomes of mathematics by 17%. While partially, reading interest and learning habits each have a significant influence on mathematics learning outcomes.